Odpowiedzi

Najlepsza Odpowiedź!
2010-02-27T14:17:29+01:00
A.
-x + 7 = 5x + 1
-x-5x=1-7
-6x=-6/(-6)
x=1
b.
6y + 30 = -2y - 2
6y+2y=-2-30
8y=-32/8
y=-4
c.
4z +35 = -z +5
4z+z=5-35
5z=-30/5
z=-6
d.
12x - 10 = -6x +8
12x+6x=8+10
18x=18/18
x=1
e.
2x - 2 = 4x -2
2x-4x=-2+2
-2x=0/(-2)
x=0
2010-02-27T14:18:04+01:00
A)
-x+7=5x+1
-x-5x=1-7
-6x=-6/:(-6)
x=1
b)
6y+30=-2y-2
6y+2y=-2-30
8y=-32/:8
y=-4
c)
4z+35=-z+5
4z+z=5-35
5z=30/:5
z=6
d)
12x-10=-6x+8
12x+6x=8+10
18x=18/:18
x=1
e)
2x-2=4x-2
2x-4x=-2+2
-2x=0/:(-2)
x=0